Effects of carnosine on the embryonic development and TiO2 nanoparticles-induced oxidative stress on Zebrafish - Caruso, Giuseppe; Scalisi, Elena Maria; Pecoraro, Roberta; Cardaci, Vincenzo; Privitera, Anna; Truglio, Emanuela; Capparucci, Fabiano; Jarosova, Romana; Salvaggio, Antonio; Caraci, Filippo; Brundo, Maria Violetta (Frontiers in Veterinary Science, 2023)
Oxidative stress is due to an unbalance between pro-oxidants, such as reactive oxygen (ROS) and nitrogen (RNS) species, and antioxidants/antioxidant system. Under physiological conditions these species are involved in different cellular processes such as cellular homeostasis and immune response, while an excessive production of ROS/RNS has been linked to the development of various diseases such as cancer, diabetes, and Alzheimer’s disease (AD). In this context, the naturally occurring dipeptide carnosine has shown the ability to scavenge ROS, counteract lipid peroxidation, and inhibit proteins oxidation. Titanium dioxide nanoparticles (TiO2-NPs) have been widely used to produce cosmetics, in wastewater treatment, in food industry, and in healthcare product. As consequence, these NPs are often released into aquatic environments. The Danio rerio (commonly called zebrafish) embryos exposure to TiO2-NPs did not affect the hatching rate, but induced oxidative stress. According to this scenario, in the present study, we first investigated the effects of carnosine exposure and of a sub-toxic administration of TiO2-NPs on the development and survival of zebrafish embryos/larvae measured through the acute embryo toxicity test (FET-Test). Zebrafish larvae represent a useful model to study oxidative stress-linked disorders and to test antioxidant molecules, while carnosine was selected based on its well-known multimodal mechanism of action that includes a strong antioxidant activity. Once the basal effects of carnosine were assessed, we then evaluated its effects on TiO2-NPs-induced oxidative stress in zebrafish larvae, measured in terms of total ROS production (measured with 2,7-dichlorodihydrofluorescein diacetate probe) and protein expression by immunohistochemistry of two cellular stress markers, 70 kDa-heat shock protein (Hsp70) and metallothioneins (MTs). We demonstrated that carnosine did not alter the phenotypes of both embryos and larvae of zebrafish at different hours post fertilization. Carnosine was instead able to significantly decrease the enhancement of ROS levels in zebrafish larvae exposed to TiO2-NPs and its antioxidant effect was paralleled by the rescue of the protein expression levels of Hsp70 and MTs. Our results suggest a therapeutic potential of carnosine as a new pharmacological tool in the context of pathologies characterized by oxidative stress such as neurodegenerative disorders.